Secure open wireless LAN using point to point protocol - Guay, Wei Lin (2007)
There are several approaches to achieve secure WLAN access network. One class of solution which will be commonly used is based on enhanced security within the IEEE 802.11 and WI-FI. Protected Access (WPA). In another class solution, the mobile station uses Point-to-Point Protocol (PPP) to establish a point-to-point tunnel to some devices normally located in the access network. Since PPP provides access control features independent of network or higher layer protocol and since it is a mature protocol with support on all major platform, it is also a good candidate for implementing a NAS in shared WLAN environment. To establish the PPP tunnel in a LAN environment, techniques such as low level PPP over the Ethernet protocol (PPPoE), or the higher level Point-to-Point Tunneling Protocol (PPTP) or Layer 2 Tunneling Protocol (L2TP) can be used. This research will be focus on adding an additional layer on top of WLAN MAC using PPP to increase the security. The work will be carried out on WLAN testbed connected to the Internet.